Heightened vulnerability to HIV among key populations during the COVID-19 crisis: a formative assessment in Mozambique (2022) - Hélder Filipe Fumo; Auria Ribeiro Banze; Cynthia Semá Baltazar (BMC Health Services Research)
Abstract Background In recent years, the intersecting challenges of AIDS, COVID-19, economic instability, and humanitarianism have significantly hindered the advancement of HIV/AIDS mitigation strategies, especially in key populations (KPs) within low-to middle-income nations. This formative study aims to evaluate the direct and indirect impacts of the COVID-19 pandemic emergency measures on HIV/AIDS prevention and treatment services for key populations in Mozambique. Methods In the first quarter of 2022, we conducted a qualitative study across six provinces in Mozambique: Maputo Province, Maputo City, Gaza, Inhambane, Manica, and Zambezia. Our study involved a diverse group of key informants (KI), including men who have sex with men (MSM), people who inject drugs (PWID), female sex workers (FSW), members of community-based organizations (CBO), police, and healthcare professionals specializing in KP. The assessment employed standardized scripts for key informant interview (KII) and focus group discussion (FGD), primarily assessing risk behaviors and access to health services since the start of the COVID-19 state of emergency in March 2020. Data collection continued until reaching saturation, and the analysis followed grounded theory principles in qualitative research. Results A total of 126 interviews were conducted, comprising 100 key informant interviews (KIIs) and 26 focus group discussions (FGDs). FSW expressed concerns about discontinuing antiretroviral treatment (ART) due to fears of COVID-19 transmission at healthcare facilities, and there was a decrease in the availability of HIV testing and prevention services at hotspots due to restrictions on HIV testing brigades. MSM observed reduced HIV education and training within CBOs. PWIDs highlighted the suspension of collective therapy sessions, while healthcare providers pointed out the halting of KP-focused health promotion coordination meetings during the emergency period. Conclusion The COVID-19 pandemic underscores the urgent need for health systems to implement flexible, adaptive service delivery models for KPs. The study’s findings call for immediate action to ensure the continuity and accessibility of HIV/AIDS services amidst ongoing global health emergencies, highlighting the importance of resilience in health service planning and execution.